Evaluation of the Pancasila Student Profile Strengthening Project (PSPSP) with the Employment Theme at the Palembang National Cadre Health Vocational School Based on the CIPP Model - Saleh Hidayat; Agung Wijaya; Candra Dwinata; Wulandari Saputri; Bagas Rasid Sidik (CV. Creative Tugu Pena, 2026)
This study aims to evaluate the implementation of the Pancasila Student Profile Strengthening Project (PSPSP) on the theme Employment at the Kader Bangsa Health Vocational School in Palembang, the CIPP evaluation model is used. (Context, Input, Process, Product). The evaluation was conducted on three groups of respondents, namely principals, teachers, and students, using a Likert scale instrument. The evaluation results showed that the Context aspect obtained high scores from all respondents, indicating the suitability of the work theme with the school's vision and students' needs. The Input received very good ratings, especially from students, which indicates the availability of adequate resources and supporting facilities. The Process aspect, how that the program implementation is running effectively but requires improvement in technical and managerial aspects. Meanwhile, the Product aspect achieved the highest score, reflecting the program's success in shaping students' character and work skills. The overall average score indicated a high level of success, with principals (88.46%), teachers (89.74%), and students (90.54%). Thus, the P5 Employability project was deemed successful in strengthening the values of the Pancasila Student Profile and relevant in the context of vocational education in vocational schools.